Type 2 Diabetes Mellitus: The Role of Oxidative stress and Antioxidants - Madhikarmi, Nirjala Laxmi; Panjijyar, Shambhu Kumar; Gautam, Madhav (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Diabetes mellitus is a group of metabolic disease characterized by hyperglycemia. Oxidative stress contributes to the pathogenesis of diabetic microvascular and macrovascular complications. This study was undertaken to find the oxidative stress and antioxidant conditions in diabetic and healthy individuals. Method: A case-control study was carried out at Kantipur Dental College Teaching Hospital & Research center, Kathmandu, Nepal from January 2018 to January 2019 with 200 subjects. Amongst them 100 were diagnosed as diabetic individuals and rest 100 were healthy controls with age and gender matched. Blood samples were drawn after overnight fasting for the analysis of glucose, thiobarbituric acid reactive substances (TBARS), lipid hydroperoxides, nitric oxide, total antioxidant activity, vitamin A, vitamin C, vitamin E, reduced glutathione, glutathione peroxidase, superoxidase and catalase. Result: The plasma glucose, lipid peroxidation parameters: TBARS, lipid hydroperoxide and nitric oxide were increased in diabetic patients. Antioxidants markers included: total antioxidant activity, reduced glutathione, vitamins A, C & E levels were significantly decreased in diabetic patients compared to healthy control counterpart. Conclusion: Increased evidence of free radicals/ oxidative stress with respect to decreased levels of antioxidants has implicated a strong role in progression of diabetes and its associated complications. Appropriate medications with antioxidants supplementation, physical exercise, and restricted diet can improve diabetes through the reduction of oxidative stress. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 454-458